Meteorological ingredients of heavy precipitation and subsequent lake-filling episodes in the northwestern Sahara - J. C. Rieder; J. C. Rieder; J. C. Rieder; F. Aemisegger; E. Dente; E. Dente; M. Armon; M. Armon (Hydrology and Earth System Sciences)
The dry Sahara was potentially wetter in the past during the warm African Humid Period. Although debated, this climatic shift is a possible scenario in a future warmer climate. One major line of evidence reported for past green periods in the Sahara is the presence of paleo-lakes. Even today, Saharan desert lakes get filled from time to time. However, very little is known about these events due to the lack of available in situ observations. In addition, the hydrometeorological conditions associated with these events have never been systematically investigated. This study proposes filling this knowledge gap by examining the meteorology of lake-filling episodes (LFEs) of Sebkha el Melah – a commonly dry lake in the northwestern Sahara. Heavy-precipitation events (HPEs) and LFEs are identified using a combination of precipitation observations and lake volume estimates derived from satellite remote sensing. Weather reanalysis data are used together with three-dimensional trajectory calculations to investigate the moisture sources and characteristics of weather systems that lead to HPEs and to assess the conditions necessary for producing LFEs. Results show that hundreds of HPEs occurred between 2000 and 2021, but only six LFEs eventuated. The ratio between the increase in lake water volume during LFEs and the precipitation volume during HPEs that triggered the lake filling, known as the runoff coefficient, provides a very useful characteristic to assess storm impacts on water availability. For the six LFEs investigated in this study, the runoff coefficient ranges across 5 orders of magnitude, much lower than the ratios often cited in the literature for the Sahara. We find that LFEs are generated most frequently in autumn by the most intense HPEs, for which the key ingredients are (i) the formation of surface extratropical cyclones to the west of the North African Atlantic coast in interplay with upper-level troughs and lows, (ii) moisture convergence from the tropics and the extratropical North Atlantic, (iii) a pre-moistening of the region upstream of the catchment over the Sahara through a recycling-domino-process, (iv) coupled or sequential lifting processes (e.g. orographic lifting and large-scale forcing), and (v) the stationarity of synoptic systems that result in long-duration (typically 3 d) HPEs. Based on the insights gained into Saharan LFEs in the present-day climate, we suggest that the initial filling and persistence of Saharan lakes may be related to changes in the intensity, frequency, or synoptic pattern of HPEs rather than to a change in mean precipitation alone. Future studies can leverage these insights to better assess the mechanisms involved in the greening of the Sahara in the past and, potentially, in a warmer future.